2015
DOI: 10.1007/s10762-015-0204-2
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Radiation Boundary Conditions in Gyrotron Oscillator Modeling

Abstract: A numerical procedure to implement a frequency-independent generalized non-reflecting radiation boundary conditions, GNRBC, based on the Laplace Transform, is described in details and tested successfully on a simple 2 frequency test problem. In the case of non-stationary regimes occurring in gyrotron oscillators, it is shown that the reflection at frequencies significantly separated from the carrier frequency can be effectively suppressed by this method. A detailed analysis shows that this numerical approach c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Contrary to the linear model presented above, the non-linear model includes the electron beam velocity and energy spreads. The code TWANG-PIC has been validated and it has been shown that it is well suited to treat non-stationary regimes [23,24].…”
Section: Modelmentioning
confidence: 99%
“…Contrary to the linear model presented above, the non-linear model includes the electron beam velocity and energy spreads. The code TWANG-PIC has been validated and it has been shown that it is well suited to treat non-stationary regimes [23,24].…”
Section: Modelmentioning
confidence: 99%
“…Such a case is present, for example, in the case of non-stationary oscillation on a single transverse mode, as was observed experimentally for the case of a gyrotron, which had been designed for Dynamic Nuclear Polarization (DNP)-enhanced Nuclear Magnetic Resonance (NMR) spectroscopy. On this gyrotron, nanosecond-pulses were observed, [22][23][24] which result in a very strong and fast variation of the field-profile. Another situation, in which the model of TWANG is no longer valid is in the case of dynamic After-Cavity-Interaction (ACI), [25][26][27] for which there are weak and unclear experimental evidences.…”
Section: Code Description and Modelmentioning
confidence: 96%
“…For this study, the above-mentioned case of a gyrotron cavity (frequency f RF % 260 GHz, power P rad 150 W) designed for DNP-NMR spectroscopy 22,23,30 was chosen, where simulations can be compared to experimental results. The geometry of the interaction region together with the inhomogeneous magnetic field profile are presented in Fig.…”
Section: A Code Benchmarkingmentioning
confidence: 99%
“…More general frequency-independent non-reflecting boundary conditions have been recently implemented in the model 16 , permitting to extend the validity domain of the model to non-stationary regimes 17,18 . The two normalized variables are the normalized axial positionẑ = ω0 c z and the normalized time τ = ω 0 t. ω 0 is a reference frequency herein chosen as the cutoff frequency in the constant radius cavity section and c is the speed of light.…”
Section: Model Descriptionmentioning
confidence: 99%